Integrated Use of Space, Geophysical and Hyperspectral Technologies Intended for Monitoring Water Leakages in Water Supply Networks - Hadjimitsis, Diofantos G.; Agapiou, Athos; Themistocleous, Kyriacos (IntechOpen, 2014)
Remote sensing has been used for water management purposes over the years. This book describes the combination of satellite imagery, in-situ spectroradiometric data and radar techniques for the identification of water leakages in the water supply network in both rural and urban areas in Cyprus. This book presents a holistic approach combining new technologies for a complete system of water distribution network leakage detection management, by combining Global Navigation Satellite Systems (GNSS), Geographical Information Systems (GIS), Satellite Remote Sensing techniques as well Geophysical surveys such as ground penetrating radar (GPR), Unmanned Aerial Vehicles (UAV) and spectro-radiometric measurements, which can be used to effectively identify and monitor water leakages.